Evaluation of real estate valuation given in graduate and postgraduate level within the scope of the valuation license exam - Polat, Zeynel Abidin; Alkan, Mehmet (Geomatik Journal, 2021)
In this study, it is aimed to make a general assessment of graduate and postgraduate education of real estate appraisal, and it has been analysed whether this education meets the content of capital market licensing exam topics. The web pages of 28 state and foundation universities that provide real estate valuation training were investigated between 01.01.2019 and 01.04.2019. These universities are grouped as universities providing valuation education courses, at the graduate and postgraduate level. The fact that the study is done through the websites. Also, the information on some departments is not reached is the limitation of the study. In the research; compulsory/elective courses and academic staff are examined in the curricula of graduate and postgraduate programs. In the study, when the 16 universities that provide course-based immovable valuation training are examined, it is seen that the number of courses given as compulsory and elective is close to each other. Besides, these courses are given in the 7th and 8th semester. The course contents are prepared mainly for the subjects of SPL licensing exam subject to the Real Estate Legislation and Real Estate Valuation Principles. Other exam topics are mentioned in part. Six universities provide education at the graduate level. When the graduate educational contents of these universities are examined, it is seen that most of the courses are given as mandatory. When the undergraduate educational contents of these universities are examined, it is seen that most of the courses are given as mandatory. When the distribution of the courses is examined, although there are predominantly subjects related to the Real Estate Legislation and Real Estate Appraisal Principles, there are also some other topics. The number of universities offering postgraduate education is 4. All of the training is covered by non- thesis master. The other two master's program courses are weighted by the Real Estate Legislation and Real Estate Valuation Principles. At the end of the research; encouraging the provision of real estate valuation as bachelor's degree, enriching the academic staff in terms of other professional groups other than map engineering (e.g. Construction Engineering, City and Regional Planning, Economics), It has been proposed to do with thesis.
Keywords: Real estate valuation; Graduate education; Valuation expertise; SPL; Geology; Remote Sensing